2020
DOI: 10.3390/jcm9103114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrasilicone Bevacizumab Injection in Diabetic Tractional Retinal Detachment Surgery: A Retrospective Case-Control Study

Abstract: Tractional retinal detachment (TRD) causes visual loss in diabetes mellitus patients. Silicone oil can be used as a tamponade to repair retinal detachment; however, intrasilicone injection is challenging. We aimed to evaluate the effect of intrasilicone bevacizumab injection in TRD surgery. This was a single-hospital, retrospective, case-control study of 44 patients (46 eyes). We reviewed medical histories and ophthalmic examination results. We administered silicone oil to 26 eyes (group I), and a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Two, both published in the European Vitreoretinal Society (EVRS) Educational Electronic Journal, where irretrievable from Queen’s University library (Belfast, UK) and The British Library (London, UK) and could not be assessed. After full-text evaluation of all other studies, 38 (with 3839 eyes) were found eligible and included . Patients had a median (IQR) age of 52.2 (49.6-55.7) years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two, both published in the European Vitreoretinal Society (EVRS) Educational Electronic Journal, where irretrievable from Queen’s University library (Belfast, UK) and The British Library (London, UK) and could not be assessed. After full-text evaluation of all other studies, 38 (with 3839 eyes) were found eligible and included . Patients had a median (IQR) age of 52.2 (49.6-55.7) years.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis of overall final VA included 20 studies 5,17,19,[22][23][24][26][27][28]30,[32][33][34]36,37,39,44,45,50,51 (1526 eyes). The pooled final BCVA was 0.94 (95% CI, 0.82-1.05) logMAR (approximate Snellen equivalent, 6/53; 95% CI, 6/39-6/71) (Figure 2).…”
Section: Outcomes Of Trd Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…PPV'nin hemen bitiminde göz içi silikon ile birlikte yarım doz intravitreal Anti-VEGF enjeksiyonu da yapılabilmektedir. [21] KTRRD' de makulanın yatışıklığı cerrahi başarıyı etkileyen önemli bir faktördür. Storey ve ark.…”
Section: Diyabetik Kombine Traksiyonel-regmatojen Retina Dekolmanında...unclassified